Kemampuan Smash Bola Voli pada Peserta Klub FVC Kota Lubuklinggau - Santika, Titis; Suhdy, Muhammad; Remora, Hengky (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to describe the basic technique of smashing the participants of the volleyball club FVC Lubuklinggau City. This type of research used descriptive quantitative. The population of all FVC club participants in Lubuklinggau City and the sample using a purposive sampling technique were 14 female participants. The method used is a survey method with data collection techniques using tests and measurements. Collected data were analyzed using the t-test at a significant level α = 0.05. Based on the results of the research that has been obtained, it can be concluded that the volleyball smash ability of the FVC Volleyball club participants in Lubuklinggau City is lacking with consideration of the average of 13.71. The volleyball smash ability of female participants in the volleyball club FVC Lubuklinggau City was in the very poor category at 21.43% (3 athletes), the less category was 7.14% (1 athlete), the sufficient category was 57.14% (8 athletes), the good category was 14.29% (2 athletes), and the very good category was 0% (0 athletes). Keywords: Volleyball, Ability, Smash